FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU KELUARGA SADAR GIZI (KADARZI) - Nita Tri Putri; Sari Ida Miharti; Viola Okta Yusenda (Universitas Fort de Kock Bukittinggi, 2022)
Poor nutrition is major problem in Pasar Baru Community helath center any 19 toddler experience the poor Nutrition. This study aimed to determine nutrition conscious behavior in Pasar Baru Community health center. Pesisir Selatan district 2019. The type of this study was descriptive with analytic cross sectional study design. it was conducted on March-June 2019. The population were mother who had a toddler in Pasar Baru Community Health Center. They were 2231 people. by using proportional random sampling, 96 people were chosen as the samples. The data were collected by using questionnaire. Then it was Analyzed by univariate and bivariate statistical test by using chi-square analysis. The results showed that 49.0% of respondents did not include Kadarzi category, 47.9% of them had low knowledge, next 42.7% of them had negative attitude, next 38.5% of them had low motivation. After that 45.8% of them sad the cadres were not active. There was a correlation between knowledge (p = 0.000, OR = 16), attitude (p = 0.000, OR = 16), motivation (p = 0.002, OR = 4), activeness cadres (p = 0.018, OR = 3) toward behavioral Kadarzi. In short it can be concluded that the knowledge, attitudes, motivation, and the liveliness of cadres had a significant relationship toward Kadarzi behavior. Then, isb expected that health workers can provide information about Kadarzi in the community in order to increase knowledge, and health workers and health volunteers motivate people to have Kadarzi. Keywords : Kadarzi, Knowledge, Attitude, Motivation and liveliness cadres.